"الأساس القانوني للعلاقات الرابطة بين أطراف الاعتماد المستندي في إطار تمويل التجارة الخارجية" (مجلة الواحات للبحوث والدراسات, 2021)
The Documentary Credit Shall Be Opened By The Bank Of The Credit Agent By Order Of The Competent Importer, For The Benefit Of The Beneficiary, Which Means That There Can Be No Documentary Credit Contract In The Absence Of Any Of These Three Parties That Are Major Parties To The Contract Of Accreditation, Documentary Credit Lies In The Fact That These Parties Do Not Meet In A Single Contract Board Other Than The Commissioner And The Bank Is Open To Credit, But During The Execution Of The Contract Other Parties Do Not Participate In It.In Addition To The Fact That These Parties Have Specific Legal Relations, Each Party Has A Special Relationship With The Other Party. The Relationship Between The Beneficiary And The Client Is Reflected In The Contract Of Sale Between Them Accreditation. Keywords - Documentary credit, Banks, indepence principleThe role of Political parties in political participation' culture, case study of Tunisia